2014
DOI: 10.1111/ggi.12298
|View full text |Cite
|
Sign up to set email alerts
|

Self‐rated health and associated factors among older people living alone in Shanghai

Abstract: Identifying factors associated with the self-rated health of older people living alone could inform the delivery of appropriate health and social care interventions to promote older people's health.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
36
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(42 citation statements)
references
References 48 publications
4
36
0
2
Order By: Relevance
“…Culture, lifestyle, environment, and disease patterns were all different in different cities, 26,27 which may also potentially influence both SRH and heart disease. [28][29][30][31][32][33] However, positive associations existed across all subgroups, and SRH may be a reliable measurement for predicting IHD risk.…”
Section: Discussionmentioning
confidence: 99%
“…Culture, lifestyle, environment, and disease patterns were all different in different cities, 26,27 which may also potentially influence both SRH and heart disease. [28][29][30][31][32][33] However, positive associations existed across all subgroups, and SRH may be a reliable measurement for predicting IHD risk.…”
Section: Discussionmentioning
confidence: 99%
“…Prevalence rates for positive self-rated health among Brazilian population-based studies varied from 24.7 to 89.1% 1,4,7 , while in international studies they varied from 35.7% to 63% 8,9,10 .…”
Section: Saúde Do Idoso; Autoavaliação; Estudos Transversaismentioning
confidence: 93%
“…A single item is a commonly used method to assess people's overall perceptions of their health. It is recommended because participants find it easier to understand and it minimises the research burden (Chen et al, ).…”
Section: Methodsmentioning
confidence: 99%
“…Further most of the studies were conducted in Western countries, in Hong Kong or Taiwan with only a few conducted in Mainland China. One study explored the SRH (Chen, While, & Hicks, ), loneliness and social support (Chen, Hicks, & While, ) of older people living alone in Shanghai, China and found that few older people considered themselves in poor health, but they reported a moderate level of loneliness and a low level of social support. However, the sample was from an economically deprived and agriculture‐dominated district.…”
Section: Introductionmentioning
confidence: 99%